2019
DOI: 10.1371/journal.pone.0222756
|View full text |Cite
|
Sign up to set email alerts
|

Confronting pastoralists’ knowledge of cattle breeds raised in the extensive production systems of Benin with multivariate analyses of morphological traits

Abstract: Cross-border seasonal livestock movements in West Africa bring into close contact several cattle breeds. In the coastal countries hosting migrating herders from the Sahel, it often affects the genetic variability and geographical distribution of traditional cattle breeds, through their indiscriminate but also intended crossbreeding with larger-framed Sahelian cattle breeds. The need to secure and effectively manage this genetic variability, in order to respond to changing production and market conditions, is w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Multivariate discriminant analyses of morphological traits have been reported, in several previous morphometric studies, to be effective for a precise and objective discrimination of different population of cattle [22][23][24][25][26][27][28], goat [29][30][31][32][33][34], sheep [16,[35][36][37], horses [38] and camel [39].…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate discriminant analyses of morphological traits have been reported, in several previous morphometric studies, to be effective for a precise and objective discrimination of different population of cattle [22][23][24][25][26][27][28], goat [29][30][31][32][33][34], sheep [16,[35][36][37], horses [38] and camel [39].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, locally adapted animals are required to cope with the various instabilities in production environments, but the indigenous Shorthorn cattle in Benin are increasingly threatened. The trypanotolerant taurine cattle (without any Zebu ancestry) reported in the region by MacHugh et al (1997) and Hanotte et al (2002) are progressively replaced by crossbreeds and trypanosusceptible Zebu cattle, including White Fulani, Sokoto Gudali, and Red Bororo ( Dossa and Vanvanhossou, 2016 ; Houessou et al, 2019b ; Ahozonlin and Dossa, 2020 ). In consequence, significant adoption of prophylactic measures is observed in Beninese herds dominated by crossbreed and Zebu cattle in comparison to other local herds ( Houessou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…3a-c). Recently, Houessou et al (2019) confirmed the accuracy of farmers' knowledge in distinguishing cattle breeds in Benin based on morphologic traits. In addition, recent genomic analyses showed very low admixture in animals identified by farmers and sampled as Somba cattle (Scheper et al 2020).…”
Section: Sampling Procedures and Data Collectionmentioning
confidence: 81%